The Sustainable Development of Ethnographic Tourism as a Means of Preservation and Post-War Recovery of Ethnocultural Heritage of Ukraine - Нaponenko Hanna I.; Yevtushenko Olena V.; Shamara Irina M.; Sychuhova Inna S. (Bìznes Inform, 2023)
Based on the analysis of the main trends in the development of the tourism market in the context of global digitalization, intensified in the field of tourism and hospitality, the article substantiates structural changes in the market of tourism services in Ukraine. The subject of the research is the prospects for sustainable development of ethnographic tourism as a means of preserving and post-war recovery of the ethnocultural heritage of Ukraine. The aim of the article is to develop a conception of sustainable development of ethnographic tourism for the post-war recovery of the ethnocultural heritage of Ukraine. The achievement of the declared aim necessitated the solution of the following tasks: to study the essence of the conception of ethnographic tourism as a form of presentation of ethnocultural heritage; to define the directions of ensuring the sustainable development of ethnographic tourism; to develop a conception of sustainable development of ethnographic tourism as a means of preserving and post-war recovery of the ethnocultural heritage of Ukraine. As a methodological basis, an integrated approach to the problems under study was adopted. In the process of research, general scientific techniques and methods of logical and comparative analysis, as well as methods of generalization and processing of information using the techniques of economic and statistical analysis were used. The article proposes the formation of the conception of ethnographic tourism in the regions of Ukraine on the basis of the use of the sharing model as a factor in increasing the sustainability of the economy. The use of the sharing model to unite and promote the services of entrepreneurs in the field of tourism and ethno-tourism resources will attract a large number of consumers of tourist services to the region, interest the youth audience, and reduce the cost of forming tour packages.